Emerging business models in agroecological tourism: the role of public policies in promoting sustainability - Fernández, Alfonso José (Cooperativismo & Desarrollo, 2025)
This study explored the crucial role of public policies in promoting emerging business models within agroecological tourism, a sector that merges agriculture and tourism to foster sustainable development in rural areas. Employing a descriptive qualitative methodology based on a systematic review of 12 relevant scientific articles published between 2020 and 2025, the relationship between policies, business models, and agroecological tourism was analyzed. The findings revealed a growing interest in Latin America, particularly in Colombia and Ecuador, with a focus on policies that encourage community participation, environmental conservation, and agricultural resilience. Business models based on circular economy, innovation, and the integration of socio-cultural-environmental aspects were identified as key to success. The research concludes that effective public policies are essential for driving agroecological tourism, as they empower communities, protect biodiversity, and foster responsible businesses, achieving a balance between economic and cultural benefits.